Black Literature and Its Tenets as Portrayed in Toni Morrison’s Novels - Dhobi, Saleem (Patan Pragya, 2023)
This paper studies Toni Morrison’s jottings to probe into different dynamics bedded into her vital novels. Since Morrison established her place within the American erudite jotting has been for the utmost part well entered both by her critics and then, her best-dealing and award- winning status for her literature testifies significance as one of the most fat and talented pens of the twentieth and twenty-first centuries. Still, because of diversity and changeable nature of her jotting, she has also been blamed negatively by numerous. One of them is the complexity of her language use. The objective of the paper has been to explore the tenets of Black Literature that differs from the American literature in general. How the writers of color including Toni Morrison outline a fictional world that shelters the characters like Beloved and Sula who surpass the common understanding about the people of color has been the focus of the article.